Case Report: Recombinant human growth hormone therapy in a patient with spondyloepiphyseal dysplasia, Kondo-Fu type - Congli Chen; Congli Chen; Jin Wu; Jin Wu; Ying Liu; Ying Liu (Frontiers Media S.A., 2023)
BackgroundVariants in membrane-bound transcription factor peptidase, site 1 (MBTPS1) gene, can result in clinically rare spondyloepiphyseal dysplasia of Kondo-fu type (OMIM #618392, SEDKF), Silver-Russell syndrome, and CAOP (cataract, alopecia, oral mucosal disorder, and psoriasis-like) syndrome.Case presentationA 6-year-old Chinese male child diagnosed with SEDKF underwent 3 years of growth hormone therapy. A genetic examination revealed two new nonsense variants in the MBTPS1 gene on chromosome 16q23-q24 with compound heterozygotes c.1589(exon12)A > G and c.163(exon2)G > A.ConclusionThe MBTPS1 gene c.1589(exon12)A > G and c.163(exon2)G > A on chromosome 16q23-q24 is associated with SEDKF. Growth hormone therapy can repair growth retardation in patients with spondyloepiphyseal dysplasia, Kondo-Fu type; however, more evidence of such patient cases is required to support this hypothesis.